STUDY OF VITAMIN-D AND HOMOCYSTEINE IN TYPE-2 DIABETES - G.S.R.KEDARI; G.S.R.HAREESH (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Diabetes mellitus is the most common endocrine disorder in developed countries and also in developing countries like India. It has been hypothesized that vitamin D levels and homocysteine levels may contribute in the pathogenesis of diabetes. The aim of our present study is to evaluate the role of vitamin D and homocysteine in type-2 diabetes. We tried to assess 25 hydroxy vitamin- D Levels by CLIA method and homocysteine by ELISA method. For this, we have taken 50 cases of type-2 diabetic patients and 75 patients as controls. A significant decrease in the levels of vitamin-D and significant increase in the levels of homocysteine were observed. This suggests that vitamin-D and homocysteine may play a role in development of type-2 diabetes mellitus. KEYWORDS Vitamin- D, Homocysteine, Diabetes mellitus.